(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article highlights the importance of depression in modern medicine and the role of innovative technologies and care in its treatment. Depression is a widespread mental disorder globally that negatively affects a person’s quality of life, social activity, and work capacity. The article analyzes digital therapeutic applications, telepsychiatry, artificial intelligence–based monitoring, neurostimulation methods, and modern pharmacological approaches based on scientific sources. In addition, the role of nursing care, psychotherapy, and psychosocial support in depression is also discussed. Integrating innovative technologies with comprehensive care helps accelerate the recovery process of patients and improves their quality of life.